Phenolic profile and protective role of Calendula officinalis against molybdenum-induced toxiciy in Allium cepa - Fatih Kutluer (Scientific Reports)
Abstract In this study, the protective effect of Calendula officinalis flower extract, which has many pharmacological and biological activities against molybdenum toxicity was investigated. Molybdenum toxicity and the protective effect of the extract were determined by Allium test. For this purpose, six different groups were formed and the protective effect was determined by determining the decrease in toxic effects on morpho-physiological, biochemical, cytogenetic and anatomical parameters induced by molybdenum. The phenolic component content of C. officinalis flower extract was also determined by LC-MS/MS analysis and correlated with the protective effect. Molybdenum caused a multifaceted toxicity in Allium cepa; a decline in physiological development, a decline in germination percentage to 73%, accompanied by a significant reduction in root length and weight gain values in comparison to the control values. Molybdenum-treated group exhibited an increase in malondialdehyde, superoxidase and catalase activity, reaching 2.51, 1.68, and 2.64 times the levels observed in the control group, respectively. In this study, it was determined that the mitotic index decreased by 25.7% in the molybdenum -treated group compared to the control group, and it also significantly increased the micronucleus level. These molybdenum-induced abnormalities were regressed by C. officinalis extract application and this protective effect was dose-dependently accelerated. The decrease in root elongation, a critical parameter in physio-morphological development, was regressed in the range of 6.75–20.6% with extract application. In the genotoxic parameters of fragment, bridge, and micronucleus frequencies, 100 µg/mL C. officinalis extract application provided protection ranging from 25.8 to 34.9%, while 200 µg/mL C. officinalis extract showed protection ranging from 37.7 to 62.4%. Malondialdehyde level, superoxide dismutase and catalase activity values decreased by 37.76%, 23.12% and 46.97%, respectively, in the molybdenum + 200 µg/mL C. officinalis treated group. The chlorophyll a and chlorophyll b values in the same group showed improvement, reaching 1.65 and 1.87 times that of the molybdenum-treated group, respectively. In this study, the flower extract of C. officinalis exhibited notable protective effects against molybdenum-induced toxicity. These findings suggest the potential therapeutic applications of C. officinalis in mitigating metal-induced oxidative stress. Future investigations are required to further characterize and identify natural extracts with antioxidant properties, with a focus on their mechanistic pathways.